EDUKASI DAN SOSIALISASI KESIAPSIAGAAN BENCANA KEPADA ANAK-ANAK DI MIS AL-WASLIYAH DESA TIMBANG LAWAN - Mujahid, Tamimi; Sufni, Nurul; Syafiq, Zoe Zarka (Yayasan Amanah Nur Aman, 2025)
Preparedness for natural disasters is an important aspect in building community resilience, especially for vulnerable groups such as children. This study aims to describe the results of disaster preparedness education and socialization activities carried out for students at MIS Al-Washliyah Timbang Lawan Village. The method used was a descriptive qualitative approach with the implementation of activities in the form of delivering disaster material and simple evacuation simulations. The results of the activity show that students have high enthusiasm and are able to understand basic concepts about disasters, including types of disasters, causes, impacts, and self-rescue steps that must be taken when a disaster occurs. In addition, teachers and educators also showed openness to this material, considering that most of them have never participated in similar training. This activity had a positive impact not only for students as the main participants, but also for the school who realized the importance of integrating disaster education in teaching and learning activities. The conclusion of this activity confirms that disaster education from an early age is an effective strategy in building a culture of disaster awareness and preparedness at the school community level. Therefore, similar activities are strongly recommended to be carried out periodically by involving various stakeholders so that the impact is wider and more sustainable.